Kinerja Perusahaan Ditinjau Dari Faktor Non Keuangan Dan Struktur Modal - Bambang Wahyudi Wicaksono, Diyan Lestari, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to analyze the performance of food and beverage companies listed on the Indonesia Stock Exchange from the period 2009 to 2016, in terms of non-financial factors consisting of corporate governance as measured by Board Size, Independent Board of Commissioners, Audit Committee, and Concentrated Ownership. Other non-financial factors are innovation which is one of the supporting factors to improve performance. Capital structure plays an important role in improving organizational performance. To analyze the effect on organizational performance in terms of non-financial factors and capital structure, this study uses multiple linear regression with panel data. The results of this study indicate that the Board Size.